Efficiency and Productivity Performance of the National Private Banks in Indonesia - Omar, Mohd. Azmi; Abd. Majid, M. Shabri; Rulindo, Ronald (Gadjah Mada International Journal of Business, 2007)
This study investigates the efficiency and productivity performance of the national private banks in Indonesia during the period of 2002-2004. The data consist of 21 national private banks including two Islamic banks. Productivity is measured by the Malmquist Index using Data Envelopment Analysis (DEA) technique. Overall, the result shows that the Total Factor Production (TFP) Index of the national private banks has considerably increased for the whole industry, in which technical change is found to be a more important source of productivity growth to the Indonesian Banking Industry compared to efficiency change. Furthermore, the result also shows that the efficiency of two Islamic banks is above the average efficiency of the national private banks.